Each tiny spark - Cartaya, Pablo (Kokila, 2019)
Sixth-grader Emilia Torres struggles with ADHD, her controlling abuela, her mother's work commitments, her father's distance after returning from deployment, evolving friendships, and a conflict over school redistricting.